2010
DOI: 10.1088/0953-8984/22/19/195105
|View full text |Cite
|
Sign up to set email alerts
|

An extended analysis of the viscosity kernel for monatomic and diatomic fluids

Abstract: We present an extended analysis of the wave-vector dependent shear viscosity of monatomic and diatomic (liquid chlorine) fluids over a wide range of wave-vectors and for a variety of state points. The analysis is based on equilibrium molecular dynamics simulations, which involves the evaluation of transverse momentum density and shear stress autocorrelation functions. For liquid chlorine we present the results in both atomic and molecular formalisms. We find that the viscosity kernel of chlorine is statistical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The strong variation of physical properties on a molecular scale in a molecularly thin channel has motivated the proposal of a non-local viscosity kernel. 28,29 Bair et al 30 observed shear localization in high pressure flow experiments of liquid lubricants under shear. The shear bands were inclined typically at ∼20 • to the walls and occurred just before the traction ("friction") coefficient became strongly nonlinear with shear rate.…”
Section: Introductionmentioning
confidence: 99%
“…The strong variation of physical properties on a molecular scale in a molecularly thin channel has motivated the proposal of a non-local viscosity kernel. 28,29 Bair et al 30 observed shear localization in high pressure flow experiments of liquid lubricants under shear. The shear bands were inclined typically at ∼20 • to the walls and occurred just before the traction ("friction") coefficient became strongly nonlinear with shear rate.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the Dirac delta is often replaced by a Gaussian or other smoothed functionals. [35][36][37] As these functionals have an arbitrary analytic form, the exact equivalence between the Irving and Kirkwood 33 equations and the continuum equations is lost in this procedure. This loss of equivalence is unimportant when a point in the continuum corresponds to a large finite region in the molecular system.…”
Section: Theorymentioning
confidence: 99%
“…In order to decrease the statistical error in the further analysis we fit the data to a Lorentzian functional form where α and β are fitting parameters that depend on the fraction of A, x A , and η 0 (x A ) is the zero-frequency viscosity for k = 0. Equation (2) has been shown to fit viscosity kernel data well for a range of different noncharged single-component fluids [4][5][6] and is here extended to include the composition dependence. The result of the fitting is depicted in Fig.…”
Section: Parametermentioning
confidence: 99%
“…The wave-vector-dependent viscosity kernel has been predicted by mode-coupling theory [7]; however, the theoretical predictions do not agree with the data from simulations [3,4]. Nevertheless, at present, the effect of the multiscale response is understood fairly well for a range of simple single-component fluids [3][4][5][6] and glasses [8,9].…”
mentioning
confidence: 96%
See 1 more Smart Citation